Sistem Pendukung Keputusan Pemilihan Lokasi Tanah Strategis di Kota Mataram Menggunakan Metode AHP-TOPSIS - Dati Nafa Alfiana; Christian Sri Kusuma Aditya; Galih Wasis Wicaksono (Jurnal Repositor, 2023)
Land location selection is very important for investors, businessmen, the community or for newcomers. The strategic land selection decision support system in the city of Mataram using the AHP (Analytic Hierarchy Process) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) methods has the aim of providing recommendations for strategic land locations to build shops, shopping centers or boarding houses or rented houses. for investors, businessmen or newcomers. In this study, the AHP method used to determine the criteria was carried out by the AHP method while the ranking stage was carried out by the TOPSIS method. In this study using 4 criteria, namely price, location, area, risk and getting results in the first rank, namely the value of 0.792853 and the tests carried out in this study were testing the accuracy of the results with calculations using the Cross-validation and the accuracy values obtained from the combination of both methods reached 85%.